Powojenne dochodzenia policyjne we Francji, czyli próba samooczyszczenia paryskiej Prefektury Policji w latach 1944–1946 - Grabowski, Jan (Zagłada Żydów. Studia i Materiały, 2013)
After the liberation of France, French authorities decided to purge the police forces of suspected collaborators and Nazi sympathizers. The Parisian police force (numbering close to 20 000 officers and civilian employees) – by far the largest in the nation, underwent a scrutiny of the specially-created Commission d’Épuration, whose mandate extended to all members of the force active during the 1940–1944 period. All in all close to 4000 officers were vetted by the Commission, and some of them for stood accused of involvement in persecuting the Jews. The officers involved were usually able to deflect the accusations, quoting orders of their superiors and lack of own initiative. Harsh verdicts in these cases were rare, and the suspects were usually treated very leniently.